Organization of Petroleum Exporting Countries, the World Trade Organization, and regional trade agreements - Desta, Melaku Geboye (2003)
Looks at OPEC and the WTO as international economic organizations. Examines whether, and how far, petroleum products are covered by the WTO. Considers the various factors which contribute to the ineffectiveness of the multilateral trading system in this sector. Highlights the recent trends towards the use of regional agreements as a solution for the problem of energy trade. Revisits the cartel question. Surveys the unilateral attempts made to challenge the legitimacy of OPEC particularly in the United States.